Witness Simulation Of Machine Breakdowns For Small, Medium And Large Aircrafts During Turnaround Process - Hashim, Nur Amanina Ayuni (Universiti Sains Malaysia, 2022)
Aircraft turnaround process included the time it took for an aircraft to arrive and depart. Some of the activities involved in an aircraft turnaround include unload and load Cargo AFT, unload and load Cargo FWD, unload and load bulk, refuelling, passenger deboarding, catering, toilet servicing, portable water servicing, head counting, cleaning, and passenger boarding. As a result, a short aircraft turnaround time is needed in order to reduce delays, which are a major concern in the aircraft business and have a direct impact on customer trust. This research was developed in response to the Kulim International Airport (KXP) project, which is currently in the development and planning stages. The aim for this project is to use Witness Horizon simulation software to analyse the aircraft turnaround procedure for three types of aircraft which is for small Airbus A320, medium Airbus A350 and large Airbus A380. In this research three distinct aircraft turnaround models were designed and analysed. There are three models which is no breakdown, breakdown on fuel machine and breakdown on both catering vehicle and fuel truck. Each model's output is examined in terms of parts, machinery, buffer, and labour performance. Each part is then compared based on the percentage of busy, idle, breakdown, average WIP, and other factors. To select the best model, a comparison table of all models was constructed. The ideal model is Model 1 (no breakdown) because it has the closest aircraft turnaround time to the projected Airbus aircraft turnaround time for actual turnaround time. Airbus A320 simulation time for Model 1 is 46 minutes, Airbus A350 for Model 1 is 50 minutes and Airbus A380 for Model 1 is 60 minutes. Model 2 and Model 3 have higher turnaround time due to breakdown of machine. Any breakdown, as modelled in the simulation for Model 2 and Model 3 will have an immediate influence on the flight schedule and cause delays.